2003
DOI: 10.1002/j.0022-0337.2003.67.10.tb03705.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Academic Integrity: Formulating Effective Honor Codes

Abstract: Academic integrity continues to be of concern in higher education as the data from undergraduate schools shows an increasing prevalence of cheating behaviors and changing values of students who are entering dental education. The use of honor codes has been reported to positively influence the attitudes and behaviors of students. This paper discusses the elements of an effective and valid honor code and its possible role in enhancing the dental school environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 16 publications
2
26
0
5
Order By: Relevance
“…Our results are consistent with others that have reported that students identify themselves as engaging in dishonest conduct because of the pressures imposed by the demands of the curriculum, which includes inflexible requirements that must be completed to graduate . The curriculum in our institution, which delays, in some cases, students a full year, encourages dishonest behaviour in students who hope to avoid the economic impact associated with an additional year of study.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with others that have reported that students identify themselves as engaging in dishonest conduct because of the pressures imposed by the demands of the curriculum, which includes inflexible requirements that must be completed to graduate . The curriculum in our institution, which delays, in some cases, students a full year, encourages dishonest behaviour in students who hope to avoid the economic impact associated with an additional year of study.…”
Section: Discussionsupporting
confidence: 90%
“…Walker 2010) and honour codes (e.g. Turner and Beemsterboer 2003) have been suggested as solutions to problems of integrity and plagiarism. Text-matching software, however, does not replace pedagogical approaches for teaching students academic writing, values and appropriate study and citation strategies (Löfström and Kupila 2013).…”
Section: Dealing With Student Plagiarism In Academiamentioning
confidence: 99%
“…Academic integrity has been defined as involving "understanding what it means to be honest in the particular culture of the academic world, and being able to apply the scholarly conventions of acknowledgment" (East and Donnelly 2012). Turner and Beemsterboer (2003) include the notions of teaching, learning and the wider academic environment, and define academic integrity as "honesty in all matters relating to endeavours of the academic environment", which includes "the teaching and learning of knowledge, skills, and values and the discovery and dissemination of new knowledge." Within the past decade, there has been a change in focus on academic integrity from detection and punishment of undesired behaviours to promotion of desired behaviours (Ferguson et al 2007).…”
Section: Introductionmentioning
confidence: 99%